Agent‐based negotiation approach for feature interactions in smart home systems using calculus of the context‐aware ambient. Issue 2 (2nd December 2019) - Alfakeeh, Ahmed S.; Al‐Bayatti, Ali H.; Siewe, Francois; Baker, Thar
Abstract: Smart home systems (SHSs) provide several services that are tailored to different residents' preferences. As a result, SHSs are highly exposed to undesirable interactions, known as feature interactions (FIs). FIs might occur as a result of a conflict in services' goals or a conflict with residents' preferences. Previous studies have proposed solutions based on applying priorities, in which some services or preferable features are disabled in favor of other services. Alternatively, the agent‐based negotiation approach (ABNA) utilizes agents and applies negotiation, enabling services with contrary features to work simultaneously. ABNA avoids applying priority between services or house residents' preferences whenever a space for a compromise exists. The mechanism of ABNA is based on the use of a hierarchy of features based on their contribution to the function of the service or on the importance of these features to house residents. To achieve a compromise between conflicting services, ABNA models services and residents by using agents, and implements a negotiation algorithm that allows services with conflicting features to work simultaneously. This paper presents a description of ABNA with a formal specification of ABNA in the calculus of context‐aware ambient (CCA). This enables the formal analysis of ABNA by using the execution environment of CCA. Abstract : A formal specification of ABNA using CCA is given. This enables the formal analysis of ABNA by using the execution environment of CCA. The pragmatics of the proposed ABNA is demonstrated using an SHS case study and the correctness of the ABNA is analyzed using ccaPL.